2009
DOI: 10.1080/01932690802553957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dispersing Agents on the Solubility of Perovskites in Water

Abstract: In this study, solubility behavior of lead magnesium niobate (PMN) powders in water was investigated in the presence of pure polyacrylic acid and polyacrylic acid/polyethylene oxide comb polymers. Experiments were performed by measuring the solubility of PMN in terms of the concentration of Pb þ2 and Mg þ2 ions in supernatant as a function of pH and dispersing agent dosage. The concentrations of the metal ions in supernatant were found to be affected by the dispersant concentration, stirring time and the suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Because both screening efficiency and bridging interactions intensify with increasing counter-ion valency, divalent counter-ions are more effective at promoting attractions between polyelectrolyte species than monovalent counter-ions. 28,29 The previous study of Şakar-Deliormanlı et al 30 showed that under fully ionized conditions (at pH 9) MgCl 2 -containing PAA solutions were only stable in the range (0-2) ×10 −2 mol L −1 MgCl 2 . At higher salt concentrations PAA starts to make complexes with Mg 2+ ions in solution and turbidity increases.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Because both screening efficiency and bridging interactions intensify with increasing counter-ion valency, divalent counter-ions are more effective at promoting attractions between polyelectrolyte species than monovalent counter-ions. 28,29 The previous study of Şakar-Deliormanlı et al 30 showed that under fully ionized conditions (at pH 9) MgCl 2 -containing PAA solutions were only stable in the range (0-2) ×10 −2 mol L −1 MgCl 2 . At higher salt concentrations PAA starts to make complexes with Mg 2+ ions in solution and turbidity increases.…”
Section: Resultsmentioning
confidence: 96%
“…The previous study of Şakar‐Deliormanlı et al showed that under fully ionized conditions (at pH 9) MgCl 2 ‐containing PAA solutions were only stable in the range (0–2) × 10 −2 mol L −1 MgCl 2 . At higher salt concentrations PAA starts to make complexes with Mg 2+ ions in solution and turbidity increases.…”
Section: Resultsmentioning
confidence: 96%